Disease control of Ralstonia solanacaerum in tomato and Xanthomonas campestris in pitaya using bacteriophage - Tan, G. H.; Tony, P. S. H. (Direct Research Journals, 2014)
Bacterial outbreaks are generally problematic to be controlled due to lack of effective bactericides and resistance development from the pathogen itself. Bacteriophages have recently been evaluated for controlling a number of phytobacteria. The efficacy test of phage incorporated with All Cosmos Industries (ACI) fertilizer for controlling tomato bacterial wilt and pitaya (dragon fruit) soft rot disease were determined. In tomato study, after two seasons of application, results indicated that 80 % of plants showed no wilting symptom was occurred. The vegetative growth of plants increased for both seasons. The survival rate of phage-cocktail in ACI fertilizer was determined and they can be detected after two months of incorporated process (7-Log PFU/ml). In pitaya study, application of phages managed to control disease spreading which caused the plants to be sustained.Treatment T1 had the highest shoot number (25.8), fruit number (0.4) and shoot length increment (12 cm) after one month of application. After four months, results showed that T1 had the highest shoot number per plant (19 cm) and shoot length increment (3.4 cm) compared to all treatments. However, there was no significant on reproductive parameters been observed. T1 performed better than Treatment T3 by 1½ and 0.7 folds in shoot number and shoot length increment, respectively. It was noted that T2 also showed some positive impacts on vegetative growth.